2017
DOI: 10.1021/acs.est.7b03331
|View full text |Cite
|
Sign up to set email alerts
|

High Quantities of Microplastic in Arctic Deep-Sea Sediments from the HAUSGARTEN Observatory

Abstract: Although mounting evidence suggests the ubiquity of microplastic in aquatic ecosystems worldwide, our knowledge of its distribution in remote environments such as Polar Regions and the deep sea is scarce. Here, we analyzed nine sediment samples taken at the HAUSGARTEN observatory in the Arctic at 2340-5570 m depth. Density separation by MicroPlastic Sediment Separator and treatment with Fenton's reagent enabled analysis via Attenuated Total Reflection FTIR and μFTIR spectroscopy. Our analyses indicate the wide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
337
3
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 708 publications
(374 citation statements)
references
References 61 publications
14
337
3
1
Order By: Relevance
“…Our experiments clearly showed that aggregates composed of biogenic particles and microplastics can be stable for several days, which makes it conceivable that such aggregates can 'survive' the often relatively long-lasting sinking to great depths without breaking apart and becoming decomposed before they reach the ocean floor. Accordingly, besides a potential transport via the food web, sinking in aggregates is very likely to be the main transport pathway that causes the presence of microplastics in deep-sea sediments observed earlier [9,11,13]. Important implications of these processes are an increased availability of microplastics to benthic organisms and a long-term accumulation of microplastics in marine sediments.…”
Section: Discussionmentioning
confidence: 99%
“…Our experiments clearly showed that aggregates composed of biogenic particles and microplastics can be stable for several days, which makes it conceivable that such aggregates can 'survive' the often relatively long-lasting sinking to great depths without breaking apart and becoming decomposed before they reach the ocean floor. Accordingly, besides a potential transport via the food web, sinking in aggregates is very likely to be the main transport pathway that causes the presence of microplastics in deep-sea sediments observed earlier [9,11,13]. Important implications of these processes are an increased availability of microplastics to benthic organisms and a long-term accumulation of microplastics in marine sediments.…”
Section: Discussionmentioning
confidence: 99%
“…2d). A possible explanation is that large plastics are prone to forces of flow and wind leading to floating on water, while smaller plastics tend to migrate into sediments and deep water [26,27]. Size distribution of group YRS and ILR in both phases is shown in Additional file 1: Table S3.…”
Section: Shape Color and Size Of Microplasticsmentioning
confidence: 99%
“…However, the growth of earthworms is meaningfully different in soil ecosystems, particularly agricultural land, contaminated with microplastics [21]. In addition, it is noteworthy that microplastics are widespread in naturally-occurring Arctic deep-sea sediments [22] and in snow ranging from the Alps to the Arctic [23]. Therefore, microplastic and nanoplastic contamination is everywhere [24].…”
Section: Introductionmentioning
confidence: 99%